Archaeology of coastal hunter-gatherer occupations in the Southern Cone - Ambrustolo, Pablo (2015)
This issue of Quaternary International contains 13 papers which are the results of a Symposium ?Arqueología de ocupaciones litorales de cazadores recolectores del Cono Sur? (Archaeology of coastal hunter-gatherer occupations in the Southern Cone) held in April of 2013 at the XVIII Argentine National Congress of Archaeology in La Rioja Province in the Northern Argentina. In this symposium, 17 papers were presented covering a vast spatial frame within Argentina, Chile and Uruguay, and different temporal scales, from middle Holocene to historical times and actualistic studies.